Model Komunikasi Pariwisata Taman Nasional Bali Barat Pada Era New Normal Berbasis E-Tourism - Asmara Dewi, Wayan Weda; Rahma Syauki, Wifka; Yunita, Primadiana; Rizky, Fadil (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
This study aims to determine how the tourism communication model of the West Bali National Park (TNBB) in the era of new normal habits. This study uses qualitative methods with observations and interviews conducted to identify Tourism Communication models to support tourism strategies in the era of new normal habits. The results of this study are the TNBB Tourism Communication Model in the New Normal era using a strategy that is not aggressive in nature, this is because the TNBB business entity itself is under the Ministry of Culture and Tourism, so that what is done is more on managing the tourist park area. Although not persuasive in its marketing communication strategy, TNBB still communicates tourism through their social media. Researchers also suggest a tourism communication strategy by collaborating the concept of ecotourism with digital technology. The concept of technology-based ecotourism will be one of the novelties in terms of TNBB tourism communication to outsiders or visitors. This concept can be done by improving the official website to be more interactive, providing virtual tours for tourists who may not yet be able to come directly to TNBB.